Stellate ganglion block used to treat reversible cerebral vasoconstriction syndrome. Issue 8 (19th April 2021) - Davis, Jeffrey; Ozcan, Mehmet S; Kamdar, Jay K; Shoaib, Maria
Abstract : Background: We present a case report of a patient who developed severe reversible cerebral vasoconstriction syndrome, which was worsening despite typical interventional and supportive care. We administered a stellate ganglion block (SGB) and monitored the vasospasm with transcranial Doppler measurements. Case report: A 25-year-old woman was admitted with recurrent headaches and neurological symptoms, which angiography showed to be caused by diffuse, multifocal, segmental narrowing of the cerebral arteries leading to severe ischemia in multiple regions. Typical treatment was initiated with arterial verapamil followed by supportive critical care, including nimodipine, intravenous fluids, permissive hypertension, and analgesia. Vasospasm was monitored daily via transcranial Doppler ultrasound (TCD). After symptoms and monitoring suggested worsening vasospasm, an SGB was administered under ultrasound guidance. Block success was confirmed via pupillometry, and repeat TCD showed improved flow through the cerebral vasculature. Improvement in vascular flow was accompanied by a gradual reduction in acute neurological symptoms, with the patient reporting no headaches the following morning. Conclusions: For patients with reversible cerebral vasoconstriction syndrome who develop severe signs or symptoms despite typical treatment, sympathetic blockade may be a possible rescue therapy. This may extend to other causes of severe vasospasm as well, and further study is needed to determine if the SGB should be included in routine or rescue therapy.